The wellbeing of First Nations children: an exploration of indicators and evaluation of a new measure - Drawson, Alexandra S. (2018)
The purpose of this project was to create, implement, and evaluate a tool designed to measure the wellbeing of First Nations children in the Robinson Superior Treaty Area. This project followed a community-based participatory research approach and was overseen by a research advisory made up of employees from the partner organization. Interviews were conducted with community members in the Robinson Superior Treaty Area and analyzed to identify indicators of wellbeing for children. This analysis was utilized to generate items for a pilot version of the measure. This pilot version was administered by two mental health intake workers to the parents and caregivers of 91 children who were seen through intake for service at Dilico Anishinabek Family Care, along with the Child and Adolescent Needs and Strengths measure (Lyons et al. 2003). Following piloting, interview with the mental health intake workers, and measure refinement, a principal component analysis was conducted and three factors emerged: General Wellbeing, Traditional Activities, and Social Engagement. This measure represents one of few created and validated for use specifically with a First Nations population and aligns with the literature regarding the importance of engagement in traditional activities and understanding of culture for the wellbeing of Indigenous people.